2020
DOI: 10.1302/2633-1462.110.bjo-2020-0135.r1
|View full text |Cite
|
Sign up to set email alerts
|

The rate of patient deferral and barriers to going forward with elective orthopaedic surgery during the COVID-19 pandemic

Abstract: Aims The primary aim was to assess the rate of patient deferral of elective orthopaedic surgery and whether this changed with time during the coronavirus disease 2019 (COVID-19) pandemic. The secondary aim was to explore the reasons why patients wanted to defer surgery and what measures/circumstances would enable them to go forward with surgery. Methods Patients were randomly selected from elective orthopaedic waiting lists at three centres in the UK in April, June, August, and September 2020 and were contacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…It has been hypothesized that patients may choose to delay, or even permanently postpone, elective arthroplasty during a global pandemic. However, Clement et al 28 demonstrated that by September 2020, the majority of patients wished to proceed with their elective orthopaedic surgery. Uncertainty regarding the numbers of patients waiting for surgery may underestimate the true scale of the problem facing elective orthopaedics in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that patients may choose to delay, or even permanently postpone, elective arthroplasty during a global pandemic. However, Clement et al 28 demonstrated that by September 2020, the majority of patients wished to proceed with their elective orthopaedic surgery. Uncertainty regarding the numbers of patients waiting for surgery may underestimate the true scale of the problem facing elective orthopaedics in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to assume that older people are more likely to postpone surgeries and operations due to the COVID-19 pandemic, as they are more susceptible to the disease than middle-aged people. Older people also have stronger health care needs than middle-aged people [ 17 ]. Further research on the COVID-19–related concerns of older individuals is needed.…”
Section: Discussionmentioning
confidence: 99%
“…They might also influence people’s health-related decisions. Specifically, these factors may directly affect anticipated behaviors that relate to people’s decisions to postpone a nonurgent surgery [ 12 , 17 ]. Therefore, this survey study aims to identify the key factors that are associated with hospitalization-related and medical service–related affective reactions and anticipated behaviors during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…They might also influence people's health-related decisions. Specifically, these factors may directly affect anticipated behaviors that relate to people's decisions to postpone a nonurgent surgery [12,17]. Therefore, this survey study aims to identify the key factors that are associated with hospitalization-related and medical service-related affective reactions and anticipated behaviors during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%